Pembelajaran Bahasa Asing Komunikatif sebagai Upaya Pemberdayaan dan Peningkatan Kemandirian Masyarakat - Siminto, Siminto (Jurnal Studi Agama dan Masyarakat, 2010)
Education plays an important role in improving the quality of human resources. One model of education that expected to produce qualified human resources, increase independence, and empower the community is learning of the foreign language. The objective of learning foreign languages is to create self-reliance and community empowerment. In other words, it is oriented to the needs of the community. By learning of that foreign language, it should be in synergy with the selection of teaching materials and appropriate learning media with the selection of appropriate teaching methods as well. Like or dislike, revolution and the selection of curriculum materials quality in foreign language learning should be done. Foreign language learning should be synergy with the subjects or courses in human resource development and entrepreneurship education, for example, they are capable of producing human resources that have the hard skills of qualified foreign language communicative, also have soft skills that make them appear to be individuals who are capable of creating self-reliance and empower people